Pancreatic Cancer Stem-like Cells Display Aggressive Behavior Mediated via Activation of FoxQ1 - Bin Bao; Asfar S. Azmi; Amro Aboukameel; Aamir Ahmad; Aliccia Bolling-Fischer; Seema Sethi; Shadan Ali; Yiwei Li; Dejuan Kong; Sanjeev Banerjee; Jessica B. Back; Fazlul H. Sarkar (2014)
Subpopulations of cancer stem cells (CSCs) or cancer stem-like cells (CSLCs) have been identified from most tumors, including pancreatic cancer (PC), and the existence of these cells is clinically relevant. Emerging evidence suggests that CSLCs participate in cell growth/proliferation, migration/invasion, metastasis, and chemo-radiotherapy resistance, ultimately contributing to poor clinical outcome. However, the pathogenesis and biological significance of CSLCs in PC has not been well characterized. In the present study, we found that isolated triple-marker-positive (CD44(+)/CD133(+)/EpCAM(+)) cells of human PC MiaPaCa-2 and L3.6pl cells behave as CSLCs. These CSLCs exhibit aggressive behavior, such as increased cell growth, migration, clonogenicity, and self-renewal capacity. The mRNA expression profiling analysis showed that CSLCs (CD44(+)/CD133(+)/EpCAM(+)) exhibit differential expression of more than 1,600 mRNAs, including FoxQ1, compared with the triple-marker-negative (CD44(-)/CD133(-)/EpCAM(-)) cells. The knockdown of FoxQ1 by its siRNA in CSLCs resulted in the inhibition of aggressive behavior, consistent with the inhibition of EpCAM and Snail expression. Mouse xenograft tumor studies showed that CSLCs have a 100-fold higher potential for tumor formation and rapid tumor growth, consistent with overexpression of CSC-associated markers/mediators, including FoxQ1, compared with its parental MiaPaCa-2 cells. The inhibition of FoxQ1 attenuated tumor formation and growth, and expression of CSC markers in the xenograft tumor derived from CSLCs of MiaPaCa-2 cells. These data clearly suggest the role of differentially expressed genes in the regulation of CSLC characteristics, further suggesting that targeting some of these genes could be important for the development of novel therapies for achieving better treatment outcome of PC.